The dependence on pressure of the velocity of ultrasonic waves in liquids and the available volume of molecules - SOCZKIEWICZ, Eugeniusz (Archives of Acoustics, 1977)
Using the Kittel formula for the pressure coefficient of the velocity of propagation of ultrasonic waves in liquids and the Kuczera formulae for the temperature coefficients of the velocity of ultrasound, a relation has been derived between the «available volume» of the liquid molecules and the repulsion exponent in the Lennard-Jones potential of the molecularinteraction. The values of the «available volume» for a number of liquids have been determined. It has also been shown that the degree of space filling increases in a homologous series of saturated hydrocarbons with the increasing number of the homologue.